Impaired protection against diabetes and coronary heart disease by high-density lipoproteins in Turks - Onat, Altan; Can, Guenay; Ayhan, Erkan; Kaya, Zekeriya; Hergenc, Guelay (W B SAUNDERS CO-ELSEVIER INC, 2009)
The issue Of whether or not incident type 2 diabetes mellitus and coronary heart disease (CHD) can be predicted by high-density lipoprotein (HDL) cholesterol in both sexes needs investigation. A representative sample of 3035 middle-aged Turkish adults free of CHD at baseline was studied with this purpose prospectively over a mean of 7.8 years. High-density lipoprotein cholesterol levels were found to be correlated in women positively with plasma fibrinogen and weakly with waist girth and C-reactive protein, and to be not correlated with fasting insulin. High-density lipoprotein cholesterol protected men against future CHID risk (for a 12-mg/dL increment: relative risk = 0.80 [95% confidence interval, 0.69-0.95]) after multivariable adjustment in logistic regression analyses for age, smoking status, physical activity grade, hypertension, abdominal obesity, diabetes, and lipid-lowering drugs. However, men were not protected against risk of diabetes. In women, HDL cholesterol was not associated with risk for CHID, whereas intermediate (40-60 mg/dL) compared with lower HDL cholesterol levels proved protective against risk of diabetes (relative risk = 0.57 [95% confidence interval, 0.36-0.90]) after adjustments that included apolipoprotein A-1 tertiles. Yet higher serum concentrations flailed to yield protection against diabetes. It Was Concluded that HDL particles confer partially lacking protection against cadiometabolic risk among Turks, and this impairment is Modulated by sex. This highly important observation may result from a setting of prevailing chronic subclinical inflammation. (c) 2009 Elsevier Inc. All rights reserved.
Keywords: APOLIPOPROTEIN-A-I; METABOLIC SYNDROME; CHOLESTEROL LEVELS; SERUM ADIPONECTIN; ARTERY-DISEASE; RISK; HDL; OXIDATION; MEN; Endocrinology & Metabolism